HARMONIZATION OF LEGISLATION ON SPORTS TRAINING AND EDUCATION: FEATURES OF THE TRANSITION PERIOD - Lubysheva, L.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the content and organization of the transition period in the implementation of legislation on the harmonization of sports training and education. Results and conclusions. In the course of theoretical analysis, the author notes the positive aspects of harmonization of sports training and the educational sphere, associated with an increase in the level of control over the form, content and methodological support of additional educational programs in this field of activity, an increase in the level of social guarantees for coaches and other specialists who acquire a pedagogical status similar to that of personnel. educational organizations. As a problematic aspect of the implementation of federal law No. 127, the distribution of financial support between sports and educational departments is given, which can lead to the loss of independence of organizations in managing financial resources to fulfill their main goals. The author concludes that the transitional period in the implementation of the new federal law on the harmonization of sports training and education makes it possible to adapt the management systems of educational and sports activities to the proposed changes in local regulations, additional educational programs for sports training, changing the legal status of the position «coach».